On Scattering for the Quintic Defocusing Nonlinear Schrödinger Equation on ℝ × 2. (19th September 2013) - Hani, Zaher; Pausader, Benoit
<x xml:space="preserve">Abstract</x> We consider the problem of large‐data scattering for the quintic nonlinear Schrödinger equation on ℝ × 2. This equation is critical both at the level of energy and mass. Most notably, we exhibit a new type of profile (a "large‐scale profile") that controls the asymptotic behavior of the solutions. © 2014 Wiley Periodicals, Inc.